A comparative study of multi criteria decision making approaches for risks assessment in supply chain. (4th December 2014) - Chand, Mahesh; Raj, Tilak; Shankar, Ravi
Risk is inherent in almost every movement of supply chain partners. With the ever-increasing push for efficiency, supply chains today are getting more and more risky. Companies need to be vigilant with the increasing risks that can harm the short-term operations as well as the long-term sustainability of their supply chain. Academic interests appear to focus mostly on the risks associated with operation of supply chain. This paper highlights four areas of supply chain-related risks, i.e., transportation risks, operations risks, supplier related risks and market related risks. The purpose of this paper is to provide a framework to proactively manage supply chain risks. This study is an effort for risks assessment in supply chain and to find out the best alternatives. For this purpose, comparative study of multi criteria decision making approaches, analytical network process (ANP) and a multi-objective optimisation by ratio analysis (MOORA) technique for order preference are used. It also addresses the insinuations for supply chain managers as they balance a concern for risks with their efforts to search for, select, develop, and manage their set of supply chain partners.